Tutela mulierum and the Augustan marriage laws - Kit Morrell (Eugesta, 2020)
This paper evaluates the impact of the Augustan marriage legislation on the legal and financial freedom of Roman women, specifically, how the introduction of the ius liberorum (the “right of children”), which granted women freedom from tutela (guardianship), affected the freedom of Roman women to deal with their property as they chose. Scholars have offered diverging views on this topic: some see Augustus’ laws as a key moment in the “emancipation” of Roman women, while others suggest that, by freeing women from tutela, the laws essentially gave legal form to existing practice. As such, the question also has bearing on the larger question of how innovations during the Augustan principate were anchored in previous law and custom. In order to shed light on these questions, this paper seeks to reconstruct the operation of tutela mulierum, in its various forms, immediately before the passage of the Augustan laws. It also considers how many women were able to claim the ius liberorum, although the nature of the evidence does not allow firm conclusions. What emerges is that the reality of tutela and the potential benefit of the ius liberorum varied widely, depending on a woman’s individual circumstances, the type of tutor she had, and especially whether she was freeborn or a freedwoman subject to a male patron; moreover, while the Augustan laws paved the way for the further weakening of tutela for freeborn women, the gap between freeborn and freed increased.